La lenga d’òc sus lo riddim - Sylvan Chabaud (Lengas)
At the end of the 1980s a new musical movement of Occitan expression developed. Its influences were linked to the arrival of rap and raggamufin, two genres that were growing at the time. Based on three important groups (Fabulous Trobadors, Massilia Sound System and Nux Vomica), each representing an Occitan city (Toulouse, Marseille and Nice), we explore here the characteristics of what is commonly known as “the artists of the Linha Imaginòt”. Their relationship with the langue d'oc, their involvement in the social sphere, their relationships and differences, their individual and collective evolution over a career spanning almost forty years : these are all avenues to try to understand the place they occupy in the history of the Chanson Occitane, between rupture and continuation.